VAR Analysis of the Exchange Rate Pass-Through Effect in Czech Republic - Borodin, Dmitry (2013)
The paper will empirically investigate the strength and the speed of the exchange rate pass-through effect in the Czech Republic, i.e. the change in the domestic prices, originally caused by the volatility of the exchange rate. VAR modelling framework has been chosen as a main instrument of analysis. Vector autoregression will also be the subject of the theoretical part of the paper, which aims to provide a clear and at the same time many-sided discussion on the relevant topics. Practical part will be completely devoted to the modelling of the exchange rate pass-through.